Evaluasi Perencanaan Produksi Kubis Di Sumatera Utara Dengan Metode Rantai Markov Waktu Diskrit - Witri Wardani Hulu; Talitha Nakhwan Hasibuan; Widya Narti Lubis; Sudianto Manullang; Sisti Nadia Amalia (Konstanta : Jurnal Matematika dan Ilmu Pengetahuan Alam, 2024)
This research aims to evaluate cabbage production planning in North Sumatra using the discrete-time Markov chain method. Cabbage is one of the horticultural agricultural products that plays an important role in North Sumatra's exports. Proper evaluation of production plans is necessary to ensure sustainability and increase productivity and export volume. The Discrete Time Markov Chain method is used to predict changes in cabbage production conditions over time by considering the factors that influence them. Data on cabbage production and harvested area in North Sumatra from 2020 to 2022 were analyzed using one-step and n-step transition opportunity matrices. The results of the analysis show that in 2023, cabbage production and harvested land area are predicted to experience a significant increase compared to the previous year. This research provides a more accurate and efficient planning strategy for cabbage production, which can ultimately improve agricultural management in North Sumatra.